2016
DOI: 10.1186/s12906-016-1322-7
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of Quercetin supplementation against Acrylamide-induced DNA damage in wistar rats

Abstract: BackgroundQuercetin (QR), is a polyphenolic flavonoid compound which is found in large amounts in certain foods, and protects against oxidative stress. The current study was conducted to determine whether Quercetin can possibly exert hepatoprotective and antioxidant activity against acrylamide (ACR) induced toxicity in rats.MethodsFour groups of Wistar rats consisting of six rats each: (i) control group; (ii) ACR treated group (50 mg/kg bw); (iii) QR group: rats were treated with QR (10 mg/kg bw); (iv) QR (10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 52 publications
6
25
0
Order By: Relevance
“…ROS is capable to cross cell membranes and react with DNA in the nucleus, 63 which contribute to changes in the cells such as increased apoptosis and proliferation, as well as in the genetic material such as rising mutation rates and genome instability. 65,67 We found that the untreated arthritic rats had higher levels of DNA damage, a match to the findings of Altindag et al, 13 where RA patients had increased DNA damage compared with healthy subjects. 13 However, we observed a significant reduction in DNA damage in groups treated with quercetin.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…ROS is capable to cross cell membranes and react with DNA in the nucleus, 63 which contribute to changes in the cells such as increased apoptosis and proliferation, as well as in the genetic material such as rising mutation rates and genome instability. 65,67 We found that the untreated arthritic rats had higher levels of DNA damage, a match to the findings of Altindag et al, 13 where RA patients had increased DNA damage compared with healthy subjects. 13 However, we observed a significant reduction in DNA damage in groups treated with quercetin.…”
Section: Discussionsupporting
confidence: 87%
“…These results indicate that quercetin scavenges ROS, thereby, decreasing DNA breaks and oxidized bases. In a study conducted by Ansar et al, quercetin decreased DNA damage in rats with acrylamide‐induced toxicity, suggesting that the antioxidant effects of this flavonoid are due to high membrane diffusion which aids the removal of oxyradicals from the lipid bilayer . Furthermore, the chelation of metal ions by quercetin is due to its pentahydroxyl structure, which eliminates lipid alkoxyl and peroxyl radicals .…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, well-known anti-oxidant properties of quercetin and (-)-epicatechin provide the protection of cellular macromolecules from damages and predict the mitochondrial dysfunction (Khan et al, 2016). In this way, studied drugs demonstrated benefit action against the development of aging-related pathologies including neurodegeneration (Shay et al, 2015; Barreca et al, 2016; Elumalai and Lakshmi, 2016), cardiovascular and liver diseases (Ansar et al, 2016; Cheserek et al, 2016), diabetes (Shay et al, 2015; Haddad and Eid, 2016), cancer (Shay et al, 2015; Khan et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“… 25 Qct has a protective effect against acrylamide-induced oxidative stress in rats. 26 Recently, the protective role of Qct against hemotoxic and immunotoxic effects of furan in rats was reported. 27 Qct has protective effects against hepatic injury by increasing plasma antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%